2020
DOI: 10.1007/s10067-019-04919-1
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness, pain, and joint counts in chronic chikungunya disease: relevance to disability and quality of life

Abstract: Introduction/Objectives-To characterize the importance of musculoskeletal stiffness in a cohort of chikungunya patients with chronic joint symptoms.Method-Eighty-two patients were followed up 3 years after chikungunya infection. Tender and swollen joint counts, a pain intensity scale, Health Assessment Questionnaire-Disability Index (HAQ-DI), and the EuroQol EQ-5D quality of life instrument were completed. A musculoskeletal stiffness questionnaire provided scores for overall stiffness and its components: stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
2
19
0
5
Order By: Relevance
“…Similar to the present results, a systematic review including different study designs (from cohort to case series, cross-sectional and case-control investigations) and comprising >6500 patients with chikungunya found that 42% (95% CI 33-51%) of these cases did not recover fully from persistent pain/arthralgia after 3 months (Paixão et al, 2018). Specifically among cohort studies, the rate of chronic arthralgia after CHIKV infection has been reported to range from 22% to 67% (Borgherini et al, 2008;Gérardin et al, 2013;Madec et al, 2013;van Genderen et al, 2016;Zeana et al, 2016;Murillo-Zamora et al, 2017;Huits et al, 2018;Watson et al, 2020). The large difference in the time elapsed between acute disease stage and patient follow-up, as well as the subjectivity in pain perception and reporting, may explain, in part, the diverse estimates of risk for development of chronic arthralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the present results, a systematic review including different study designs (from cohort to case series, cross-sectional and case-control investigations) and comprising >6500 patients with chikungunya found that 42% (95% CI 33-51%) of these cases did not recover fully from persistent pain/arthralgia after 3 months (Paixão et al, 2018). Specifically among cohort studies, the rate of chronic arthralgia after CHIKV infection has been reported to range from 22% to 67% (Borgherini et al, 2008;Gérardin et al, 2013;Madec et al, 2013;van Genderen et al, 2016;Zeana et al, 2016;Murillo-Zamora et al, 2017;Huits et al, 2018;Watson et al, 2020). The large difference in the time elapsed between acute disease stage and patient follow-up, as well as the subjectivity in pain perception and reporting, may explain, in part, the diverse estimates of risk for development of chronic arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…In this stage, arthralgia typically affects multiple joints in a relapsing-remitting or persistent pattern (Weaver and Lecuit, 2015). Other common symptoms of chronic chikungunya include joint stiffness, oedema and redness (Consuegra-Rodríguez et al, 2018;Watson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Arthralgia is the hallmark of chronic CHIKV disease. Whether continuous in nature or following a relapsing-remitting pattern, this debilitating joint pain is associated with significant disability and impaired quality of life (Elsinga et al 2017;Watson et al 2020). To-date, no commercial vaccine or specific antiviral drugs exist for the prevention or treatment of infection with CHIKV, with clinical management primarily focused on the relief of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic joint inflammation and pain are the hallmarks of disease in patients with alphavirus infections 27,45 . Pain is one of the classical signs of the inflammatory process in which sensitization of the nociceptors is the common denominator 46 .…”
Section: Discussionmentioning
confidence: 99%